2020
DOI: 10.1021/acsomega.0c02069
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Catalytic Effect of Transition-Metal Ions on the Aquathermal Degradation of Sulfur-Containing Heavy Oil: A DFT Study of Cyclohexyl Phenyl Sulfide Cleavage

Abstract: Steam injection is the most widely used technique for effectively reducing the viscosity of heavy oil in heavy oil production, in which in situ upgrading of heavy oil by aquathermolysis plays an important role. Earlier, transition-metal catalysts have been used for improving the efficiency of steam injection by catalytic aquathermolysis and achieving a higher degree of in situ oil upgrading. However, the unclear mechanism of aquathermolysis makes it difficult to choose efficient catalysts for different types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Regarding the oxidation parameter, it increases in all the samples relative to the base crude oil, especially at 300 ppm of molybdenum naphthenate. It is well known that catalysts act especially in the weakest bonds with heteroatoms (C–R, R: S, O), causing reactions such as oxygenation, alcoholization, and esterification. , ,74 Therefore, greater oxidation is associated with new species formation with functional groups that contain oxygen and sulfur as alcohols, ethers, esters, thioesters, thiols, and sulfoxides, among others. This allows corroborating that oxidation reactions are developed in the catalytic aquathermolysis tests carried out.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding the oxidation parameter, it increases in all the samples relative to the base crude oil, especially at 300 ppm of molybdenum naphthenate. It is well known that catalysts act especially in the weakest bonds with heteroatoms (C–R, R: S, O), causing reactions such as oxygenation, alcoholization, and esterification. , ,74 Therefore, greater oxidation is associated with new species formation with functional groups that contain oxygen and sulfur as alcohols, ethers, esters, thioesters, thiols, and sulfoxides, among others. This allows corroborating that oxidation reactions are developed in the catalytic aquathermolysis tests carried out.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zhong et al [5] further investigated the use of CuO nanoparticles in the catalytic pyrolysis of heavy oil and observed that the addition of a THF donor in the catalytic reaction further reduced the viscosity. Furthermore, a recent density functional theory (DFT) study [6] reported the catalytic activity of several transition metal ions in the hydrothermal degradation of heavy oil; they found the order of catalytic activity as Cu 2+ > Co 2+ ≈ Ni 2+ > Fe 2+ , with Cu 2+ exhibiting the highest catalytic activity.…”
Section: Introductionmentioning
confidence: 99%